1984
DOI: 10.1007/bf00293877
|View full text |Cite
|
Sign up to set email alerts
|

The mode of inheritance of psoriasis: Evidence for a major gene as well as a multifactorial component and its implication for genetic counselling

Abstract: Complex segregation analysis of Lomholt's family data on psoriasis on the Faroe Islands gave evidence for an additive major gene with gene frequency of 0.07 and penetrance 0.12 and 0.44 in the heterozygote and in the homozygote, respectively. In addition, there was a multifactorial component with heritability 0.87. The implications of these findings for genetic counseling are discussed and analytical risk figures are presented for chosen pedigrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…The Danish study 9 estimated the heritability of the disease to be about 90%, whereas the Australian study 10 reported the heritability of about 80%. A similar estimate of heritability (87%) was obtained from re‐analyses of the census study conducted by Lomholt on the Faroe Islands 20 . We found a slightly lower heritability (66%) of psoriasis.…”
Section: Discussionsupporting
confidence: 85%
“…The Danish study 9 estimated the heritability of the disease to be about 90%, whereas the Australian study 10 reported the heritability of about 80%. A similar estimate of heritability (87%) was obtained from re‐analyses of the census study conducted by Lomholt on the Faroe Islands 20 . We found a slightly lower heritability (66%) of psoriasis.…”
Section: Discussionsupporting
confidence: 85%
“…Both psoriasis and PsA show high rates of familial aggregation, suggesting that both disorders have a strong genetic basis (20)(21)(22)(23)(24)(25). In a landmark study by Moll & Wright (20), the prevalence of PsA among first-degree relatives was 49 times higher than the prevalence in the general population.…”
Section: Genetic Factorsmentioning
confidence: 94%
“…1,7 A multi-factorial inheritance which involves several genes has been suggested 8,9 but evidence for a major gene has also been proposed. 10 We have earlier shown in a population genetic study that a recessive mode of inheritance is compatible with distribution among first degree relatives with a high gene frequency. 11 With a recessive mode and a high gene frequency, a number of families will appear with a pseudo-dominant inheritance, ie one parent homozygous and the other heterozygous, giving a dominant-like inheritance.…”
Section: Introductionmentioning
confidence: 94%